Numerical investigation of coalescence-induced droplet jumping on superhydrophobic surfaces for efficient dropwise condensation heat transfer. (April 2016) - Cheng, Yongpan; Xu, Jinliang; Sui, Yi
Highlights: Coalescence-induced droplet jumping was simulated with diffuse interface method. Effect of contact angle on the droplet jumping was revealed. Energy conversions during droplet jumping were studied. Contact angle hysteresis had great effect on droplet jumping. Abstract: Dropwise condensation has much higher heat transfer efficiency than the filmwise condensation, hence it will be widely applied in power generation, waste heat recovery, refrigeration etc. The spontaneous coalescence-induced droplet jumping on superhydrophobic surfaces was an effective way to maintain highly efficient dropwise condensation. In our study, the coalescence-induced droplet jumping process was numerically studied through transient three-dimensional diffuse interface method. The effect of contact angle and its hysteresis, droplet size, viscosity and gravity on the jumping process was studied in details, energy conversions were also provided among the droplet surface energy, viscous dissipation, kinetic energy and gravitational energy. Our study showed that contact angle had negative effect on the jumping velocity, with the decreasing contact angle, both peak jumping velocities and radius range for droplet jumping would be reduced. For the capillary-inertial process the normalized droplet jumping velocity was at the order of 0.2. Although more than half of the released surface energy could be converted into the kinetic energy, only less than 10% of the released surface energy could be converted into the translational kinetic energy for droplet jumping. The contact angle hysteresis had significant effect on the droplet jumping, the larger advancing contact angle could help improve the droplet jumping velocity, while the lower receding contact angle could reduce the droplet jumping velocity. Our results might provide useful guideline for design of efficient dropwise condensation heat transfer through coalescence-induced droplet jumping on superhydrophobic surfaces.